Penerapan Konsep Sikap Peduli Lingkungan Kepada Anak Pesisir Ranooha Raya - Asriyana; Nurdiana A; Rosmawati; Risfandi; Afyudi, Bobby; Piliana, Wa Ode; Annaastasia, Nurhuda; Yusuf, Sarini; Ola, Onu La; Haya, La Ode M. Yasir; Lawelle, Sjamsu Alam; Oetama, Dedy (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
The most problematic issue due to the coastal zone and it seems to be like common things to happen there is about the clean of the coastal area. Coastal zone with bustling activities lean to highly environmental anthropogenic pressure and it always be the main course to destroy its system in the way of morphological and biologic terms. What the coastal people do in the living occasionally turn up to create any garbage and contamination. We can’t say no that a lot of coastal site in Indonesia has a bad condition by the appearance of the contaminant. Those kinds of conditions are tightly due to social economic situation and cultural behavior of the coastal society in which they often show some careless act to a healthiness of the area. That careless habits of course been caused by the lack of their knowledge and information about how important the soundness of the coastal-living really is. Halu Oleo University by the Faculty of Fisheries and Marine Science, in the Major of Fisheries Agro-business, has simulated an approach of the study in upgrading the awareness to the society of the coast. The phenomenological program held to develop the sense of cares to the young generations of the coastal so they can stimulate their more-growing attention to the healthiness quality of the coastal and to grow the feels of caring a coastal living-hood. It placed in Ranooha Raya Village, Sub district of Moramo, South Konawe Regency. This program contained the attachment of garbage signs, education of the coast healthiness and the act of coastal cleaning by the young people and kids in the place. A lot of villager especially young generation and kids are willingly to enjoy these activities. This approach can hopefully to be a main conduct to the young people to care more than before to the coastal area as their place of growth and the place for them to make a living in a proper way.